Menyingkap Maqasid Profetik dalam Hadis tentang Relasi Laki-Laki dan Perempuan - Umma Farida; H Hardivizon; Abdurrohman Kasdi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Revealing the Prophetic Maqasid in the Hadith About Relationships between Men and WomenThe textual reading of the Prophet's hadith about the relationship between men and women often results in discriminatory and subordinating attitudes towards certain genders. This article aims to reread the hadith about the relationship between men and women. It emphasizes the disclosure of prophetic Maqasid or the orientation and purpose of prophethood in the hadith. This study uses a descriptive-analytical method by criticizing the traditions about the relationship between men and women contained in the books of Sunan Abi Dawud, al-Tirmidzi, and al-Darimi. The result shows that revealing the prophetic Maqasid in these traditions is urgent considering that the purpose of Muhammad's sending was to spread love to the universe based on monotheism (Tawhid). Tawhid is not only a verbal statement. It becomes the main foundation in building a socio-political-cultural order that promotes equality and balance between men and women. A balanced and harmonious relationship between the two becomes the Maqasid of the Prophet in every utterance and policy he established. The balance of relations between men and women by relying on a correct and comprehensive understanding of the hadith of the Prophet opens opportunities for women to perform and play the roles that need them for the good of humanity universally